The Students Impoliteness in the English Classroom Interaction - AnisahFirly Chaniago; LiaNata Safitri; EmeliyaSukma Dara (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This research examined the impoliteness gestures used by instructors and students. The researcher observed and interviewed some students in the classroom while she gathered the data, and she used a qualitative research approach to analyze it. The research was conducted at the second semester of Junior High School in 2023/2024 academic year. The findings indicate that teachers and students both used disrespectful language during instructing. In presenting the information, the pupils preferred that the teacher use crude language. They said that using obscene language made it simpler for the pupils to comprehend the information the teacher was teaching. They claimed that using a variety of teaching methods and the teacher's language improved students' learning and comprehension significantly. According to Culpeper theory (1996), there are five strategies of impolite strategies used by students and teachers in the class. Those are (1) bald on record impoliteness (2) positive impoliteness (3) negative impoliteness (4) sarcasm or mock politeness and (5) withhold politeness.